Adaptive Immune Responses in Humans During Nipah Virus Acute and Convalescent Phases of Infection. (7th January 2019) - Arunkumar, Govindakarnavar; Devadiga, Santhosha; McElroy, Anita K; Prabhu, Suresh; Sheik, Shahin; Abdulmajeed, Jazeel; Robin, Sudandiradas; Sushama, Aswathyraj; Jayaram, Anup; Nittur, Sudheesh; Shakir, Mohammed; Kumar, Keeriyatt Govindan Sajeeth; et al.
Abstract: Background: Nipah virus (NiV) is 1 of 10 potential causes of imminent public health emergencies of international concern. We investigated the NiV outbreak that occurred in May 2018 in Kerala, India. Here we describe the longitudinal characteristics of cell-mediated and humoral immune responses to NiV infection during the acute and convalescent phases in 2 human survivors. Methods: Serial blood samples were obtained from the only 2 survivors of the NiV outbreak in Kerala. We used flow cytometry to determine the absolute T-lymphocyte and B-lymphocyte counts and the phenotypes of both T and B cells. We also detected and quantitated the humoral immune response to NiV by virus-specific immunoglobulin M (IgM) and immunoglobulin G (IgG) enzyme-linked immunosorbent assay. Results: Absolute numbers of T lymphocytes remained within normal limits throughout the period of illness studied in both survivors. However, a marked elevation of activated CD8 T cells was observed in both cases. More than 30% of total CD8 T cells expressed Ki67, indicating active proliferation. Proliferating (Ki-67 + ) CD8 T cells expressed high levels of granzyme B and PD-1, consistent with the profile of acute effector cells. Total B-lymphocyte, activated B-cell, and plasmablast counts were also elevated in NiV survivors. These individuals developed detectable NiV-specific IgM and IgG antibodies within a week of disease onset. Clearance of NiV RNA from blood preceded the appearance of virus-specific IgG and coincided with the peak of activated CD8 T cells. Conclusions: We describe for the first time longitudinal kinetic data on the activation status of human B- and T-cell populations during acute NiV infection. While marked CD8 T-cell activation was observed with effector characteristics, activated CD4 T cells were less prominent. Abstract : We describe for the first time the adaptive immune response to Nipah virus infection during the acute and convalescent phases, in the 2 lone survivors during the Nipah virus outbreak that occurred in May 2018 in Kerala, India.